Effect of the silane coupling agent on the hybrid thermoplastic natural rubber composites filled rice husk and oil palm empty fruit bunch - Ratim, Suzana; Ahmad, Sahrim; Rasid, Rozaidi (Penerbit Universiti Sains Malaysia, 2004)
The used of lignocellulosic material as replacement in composites is currently generating much interest in most application. Lignocellulosic-derived fillers have many advantages compared to inorganic fillers. The advantages of natural filler receiving increasing attention for industrial application due to cost effectiveness,low density, high specific strength, bio-degradability and free from health hazard.